FOREIGN INSTITUTIONAL OWNERSHIP ANDSTOCK RETURN VOLATILITY IN INDONESIA - Ekaputra, Irwan Adi (Jurnal Keuangan dan Perbankan, 2015)
This paper examines the impact of foreign institutional ownership on contemporaneous stock return volatility in Indonesia. In this study, return volatility is measured as standard deviation of daily stockreturns. The dynamic panel data results based on System GMM (S-GMM) estimation, confirm that foreign institutional ownership tend to linearly and convexly increase monthly stock return volatility.The linear impact seems to be weaker for stocks with higher market capitalization, but stronger for stocks with higher turnover.Furthertest reveals that foreign financial institutional ownershiplinearly contributes to return volatility upsurge, while foreign non-financial corporation ownership convexly contribute to return volatility increase.The additional test also uncovers that domestic financial and non-financial institutionalownerships do not impact return volatility.